LIR‐1 educates expanded human NK cells and defines a unique antitumor NK cell subset with potent antibody‐dependent cellular cytotoxicity. Issue 10 (5th October 2021) - Leijonhufvud, Caroline; Reger, Robert; Segerberg, Filip; Theorell, Jakob; Schlums, Heinrich; Bryceson, Yenan T; Childs, Richard W; Carlsten, Mattias
Abstract: Objective: KIR and NKG2A receptors educate human NK cells to stay responsive to cells with diminished HLA class I. Here, we addressed whether the HLA class I‐binding receptor LIR‐1 (LILRB1/ILT2/CD85j), which is widely expressed on human NK cells, can mediate education and contribute to antitumor functions of NK cells. Methods: Healthy donor NK cells either unstimulated, overnight cytokine‐activated or ex vivo ‐expanded were used to target human cell lines. Phenotype and function were analysed using flow cytometry and 51 Cr‐release assays. Results: We found that the inhibitory receptor LIR‐1 can mediate NK cell education under specific conditions. This novel finding was exclusive to expanded NK cells and further characterisation of the cells revealed high expression of granzyme B and DNAM‐1, which both previously have been linked to NK cell education. Corroborating the rheostat education model, LIR‐1 co‐expression with an educating KIR further increased the responsiveness of expanded NK cells. Inversely, antibody masking of LIR‐1 decreased the responsiveness. LIR‐1 + expanded NK cells displayed high intrinsic ADCC that, in contrast to KIR and NKG2A, was not inhibited by HLA class I. Conclusion: These findings identify a unique NK cell subset attractive for adoptive cell therapy to treat cancer. Given that LIR‐1 binds most HLA class I molecules, this subset may be explored in both autologous and allogeneic settings to innately reject HLA class I ‐ tumor cells as well as HLA class I + target cells when combined with antitumor antibodies. Further studies are warranted to address the potential of this subset in vivo . Abstract : In this study, we uncover for the first time that the leukocyte immunoglobulin‐like receptor 1 (LIR‐1) inhibitory receptor can mediate natural killer (NK) cell education under specific conditions. This was exclusive to expanded NK cells and associated with potent antibody‐dependent cellular cytotoxicity. The features of LIR‐1 + expanded NK cells make them attractive for immunotherapy across human leukocyte antigen class I barriers.